The cultivation conditions of leafy vegetables influence the structures of phyllosphere bacterial communities and ultimately impact the L. monocytogenes growth post-harvest - Culliney, Paul; Schmalenberger, Achim (Frontiers in Microbiology, 2025)
Cultivation conditions, including plant species, variety, cultivation method, and seasonality, are all at least co-factors of epiphytic Listeria monocytogenes growth. Meanwhile, phyllosphere-associated bacteria were found to influence the colonization of invading pathogens. Thus, the main objective of this study was to determine whether cultivation conditions are factors in the development of the bacterial phyllosphere community on leafy vegetables, which consequently correlates positively or negatively with L. monocytogenes growth. Indeed, this study revealed that vegetable cultivation conditions are a more significant determinant of phyllosphere development than plant species. Of the identified phyllosphere-associated bacteria, the presence of Pseudomonadaceae had a positive correlation with L. monocytogenes populations on all tested produce. Hitherto, Pseudomonadaceae content appeared to be more critical for L. monocytogenes growth on spinach F1 Trumpet. For days 7–9 of storage, Pseudomonadaceae increased abundance on open field spinach F1 Trumpet were associated with L. monocytogenes’ most significant increase (0.94 log10 colony-forming unit (cfu) g−1). In contrast, Pseudomonadaceae content decreased for polytunnel spinach F1 Trumpet, and the corresponding L. monocytogenes populations remained unchanged. Carnobacteriaceae were present on spinach F1 Trumpet from the polytunnel but not on other spinach products, with higher associated L. monocytogenes growth. Pectobacteriaceae (genus Dickeya) increased for spinach F1 Trumpet polytunnel but decreased for other spinach produce with lower associated L. monocytogenes growth. Similarly, polytunnel rocket Esmee had an increasing relative abundance of Pectobacteriaceae, whereas it remained constant for polytunnel rocket Buzz. Compared to summer spinach F1 Trumpet produce, winter produce had significantly greater Streptococcaceae content and was correlated with a decrease in L. monocytogenes growth. Finally, higher phyllosphere alpha diversity putatively limited L. monocytogenes growth. Ultimately, this study revealed that cultivation conditions determine the bacterial phyllosphere community structure, which consequently influences L. monocytogenes growth.